Effect of ultrasonic application during KOH pretreatment and anaerobic process on digestion performance of wheat straw. Issue 16 (4th March 2020) - Korai, Rashid Mustafa; Wachemo, Akiber Chufo; Yue, Liu; Jaffar, Muhammad; Li, Zhengwei; Shahbaz, Muhammad; Yuan, Hairong; Li, Xiujin
Abstract : The effect of ultrasonic application during KOH pretreatment and anaerobic digestion of wheat straw. Abstract : The digester performance was enhanced by ultrasonic application during pretreatment and the anaerobic digestion (AD) process. Two setups (with and without ultrasonic application) were applied during pretreatment and AD, to untreated and potassium hydroxide (KOH) pretreated wheat straw. The results confirmed that the ultrasonic application enhanced the hydrolysis process during pretreatment. The highest total volatile fatty acid (TVFA) (3012 ± 18 mg L −1 ) production and overall lignin, hemicellulose, and cellulose (LHC) reductions (22.4 ± 0.5%) were obtained from ultrasonic assisted KOH pretreated (KOHU ) samples, after 36 hours of pretreatment. Similarly, the SEM analysis showed obvious disruption in the outer structure of KOHU samples. However, the ultrasonic application during AD showed significant improvement in biodegradation rate, biogas and biomethane production. Obvious reduction in sonication time (76%) along with enhanced biogas (570 ± 9 mL gm −1 VS) and biomethane (306 ± 12 mL gm −1 VS) production were observed from KOH pretreated digesters, when ultrasonication was applied during AD. Moreover, the biodegradation rate reached up to 76% along with highest total solid (TS) and volatile solid (VS) reductions from digesters with single KOH pretreatment and ultrasonic influence during AD. Finally, the digester effluent ranged in between the stable values, confirming the completion of the AD process. These results suggested that ultrasonic application was more effective when applied during AD due to the higher liquid to solid ratio. The reduction in energy input can be beneficial for commercial applications and to recognize the better stage for ultrasonic application for enhanced biomethane yield.